Comparison of commercial assays and two-step approach to detect Clostridioides difficile in South Africa - Sarishna Singh; Mae Newton-Foot; Pieter Nel; Colette Pienaar (AOSIS, 2022)
Background: Clostridioides difficile is the number one cause of hospital-acquired diarrhoea. Accurate diagnosis of C. difficile is of utmost importance as it guides patient management and infection control practices. Studies evaluating the performance of commercially available nucleic acid amplification tests (NAATs) versus algorithms are lacking in resource-limited settings. Objective: This study assessed the performance of three commercially available tests and a two-step approach for the diagnosis of C. difficile infection using toxigenic culture (TC) as the gold standard. Methods: Two hundred and twenty-three non-duplicate loose stool samples were submitted to the National Health Laboratory Service Microbiology Laboratory at Tygerberg Hospital, Cape Town, South Africa, from October 2017 to October 2018. The samples were tested in parallel using the C. DIFF QUIK CHEK COMPLETE enzyme immunoassay (EIA) and two NAATs (Xpert C. difficile and BD MAX Cdiff), and the results were compared to TC. The performance of a two-step approach consisting of the C. DIFF QUIK CHEK COMPLETE followed by the Xpert C. difficile was also determined. Results: Of 223 faecal specimens tested, 37 (16.6%) were TC-positive. The sensitivity and specificity of the C. DIFF QUIK CHEK COMPLETE were 54.1% and 98.9%; Xpert C. difficile, 86.4% and 96.8%; BD MAX Cdiff, 89.2% and 96.8%; and two-step approach, 89.2% and 96.2%. Conclusion: The C. DIFF QUIK CHEK COMPLETE, in a two-step approach with the Xpert C. difficile, performed similarly to the NAATs on their own and offer advantages in terms of cost and workflow in low-resource settings.